PERENCANAAN PERKUATAN LERENG PERUMAHAN CITRALAND MANADO, SULAWESI UTARA - Fredy Aditya Yulianto; Dwiyanto Joko Suprapto; Prakosa Rachwibowo (Geological Engineering E-Journal, 2014)
Movement of soil often found in the State of Indonesia and is one of the natural disasters that can damage and harm humans each year. Indonesia most of the territory is hilly and mountainous, it is what makes our country vulnerable to catastrophic ground motion. This condition coupled with high rainfall as a trigger of ground motion. PT. Ciputra International is one company that is engaged in the development of housing. Housing development in the implementation problems encountered Citraland Manado local ground motion (local). Even landslides in Cluster 4 Eden Bridge damage homes and 6 people died. The cause of the avalanche is the presence of high rainfall and the presence of cracks in the rocks of the area. In anticipation of this problem, mapping and planning geotechnical slope reinforcement. Some of the data that is needed is the type of rock, heavy rock, fracture conditions, slope geometry, and rock mechanics of data. The lithology of the research sites is a tuff, sand gravel, volcanic breccias, soil embankment and sand. Based on the research generated sites prone to landslides for slope stability analysis is then performed using the software slides and phase2. The location of the Church of the Holy Kalam and Northern Hill still potentially complex landslide, being Cluster Eden Bridge is secure. At the location of the Church of the Holy Kalam, which meets the safety factor in both dry and water-saturated conditions are 1.423 and 1.349 which is a combination between the anchor and grouting grouting on the slopes and at the summit. While the location of the Northern Hill barrow, which meets the safety factor in both dry and water-saturated conditions are 1.505 and 1.494 which is the slope reinforcement using grouting.